Does college make you progre? Evidence from Bolivia; Te hace progre la universidad? - Antonio Saravia (Estudios de Economía, 2022)
I examine the association between college education and left-leaning views in Bolivia using novel survey data. My findings suggest that college education is associated with left-leaning social preferences (college-educated individuals favor social equality and a tax system in which not everybody must pay taxes) but right-leaning individual preferences (they favor individual liberty and respect for private property). My results fit the connotation given to terms like progre or socialista caviar commonly used in Latin America to refer to educated individuals who consider themselves progressive, or even socialist, but admit and enjoy the benefits of individual liberty and markets.
Keywords: I23; A13; P16; 330; Bolivia; education; college; public opinion; ideology